2015
DOI: 10.4103/2347-9264.153194
|View full text |Cite
|
Sign up to set email alerts
|

A survey of analgesic and anti-inflammatory drug prescription for oral implant surgery

Abstract: Aim: This study was conducted to determine the preferred analgesic and anti-inflammatory drugs prescribed by oral implantologists in India. Methods: A structured questionnaire was distributed to 332 dentists to gather information regarding their prescription habits for analgesics and anti-inflammatory drugs. Frequency distributions were computed by type of drug being prescribed and the protocol followed. Results: Analysis of data showed that majority of dentists (85.8%, n = 285) prescribed conventional non-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
2
Order By: Relevance
“…Implant procedures were associated with the highest odds for the prescription of opioids among the various dental procedures examined. This finding is in sharp contrast to reports by Datta et al (2015) in which the majority of dentists (85.8%) prescribed NSAIDs for implant surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Implant procedures were associated with the highest odds for the prescription of opioids among the various dental procedures examined. This finding is in sharp contrast to reports by Datta et al (2015) in which the majority of dentists (85.8%) prescribed NSAIDs for implant surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the actual situation in Albania, we thought that assessing dentists' knowledge and attitudes specifically on NSAIDs could give us some indications of whether there is a need to raise awareness on this topic. Despite some studies conducted in different countries on NSAIDs knowledge and prescription in dentistry, especially in pulpal and periapical pathologies (Segura et al, 2014), in oral implant surgery (Datta et al, 2015) and among dentistry students (Guzmán et al, 2012), we found no studies assessing the knowledge on NSAIDs prescription and risk factors among Albanian dentists. The aim of the study is to assess dentists' knowledge on the use, risks, and characteristics of NSAIDs, in order to evaluate whether there is a need to receive further education in NSAIDs camp to improve the well-being of their patients.…”
Section: Introductioncontrasting
confidence: 67%
“…Whatever the indication of AIDs, the treatment duration should also conform to the rules of good practice. Therefore, in order to avoid potential complications, it is essential to raise awareness among the dental practitioners of the appropriate indications and dosage regimen of specific drugs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%